Building Harmony in Diversity in Papua - Warwer, Fredrik; Malatuny, Yakob Godlif (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Papua is one of the most heterogeneous regions in Indonesia, with more than 261 ethnic groups and over 250 local languages, making it a unique laboratory of multiculturalism. This diversity presents both opportunities for harmony and risks of tension, thus requiring wise strategies for management. The Community Service Program (PkM) entitled “Building Harmony in Diversity in Papua” at IAIN Fattahul Muluk Papua aimed to strengthen awareness of tolerance, intercultural dialogue, and respect for both customary and religious values. The program was carried out through interactive lectures and discussions facilitated by the Head of STAKPN Sentani. The results revealed that harmony is not merely the absence of conflict but a dynamic process nurtured through justice, solidarity, and respect for differences. Discussions highlighted the role of students as agents of tolerance and religious leaders as social mediators. In conclusion, harmony in Papua can only be achieved if indigenous traditions, religious values, and inclusive education are consistently practiced as foundations of unity in diversity.